Breaking Down the Wall: The Strategic Plan of Cancer to Conquer the Brain. Issue 6 (November 2020) - Valiente, Manuel; M de la Prida, Liset
Pathogenesis of Peritumoral Hyperexcitability in an Immunocompetent CRISPR-Based Glioblastoma Model Hatcher A, Yu K, Meyer J, Aiba I, Deneen B, Noeb JL. J Clin Invest . 2020;130(5):2286-2300. doi:10.1172/JCI133316 Seizures often herald the clinical appearance of gliomas or appear at later stages. Dissecting their precise evolution and cellular pathogenesis in brain malignancies could inform the development of staged therapies for these highly pharmacoresistant epilepsies. Studies in immunodeficient xenograft models have identified local interneuron loss and excess glial glutamate release as chief contributors to network disinhibition, but how hyperexcitability in the peritumoral microenvironment evolves in an immunocompetent brain is unclear. We generated gliomas in WT mice via in utero deletion of key tumor suppressor genes and serially monitored cortical epileptogenesis during tumor infiltration with in vivo electrophysiology and GCAMP7 calcium imaging, revealing a reproducible progression from hyperexcitability to convulsive seizures. Long before seizures, coincident with loss of inhibitory cells and their protective scaffolding, gain of glial glutamate antiporter xCT expression, and reactive astrocytosis, we detected local Iba1+ microglial inflammation that intensified and later extended far beyond tumor boundaries. Hitherto unrecognized episodes of cortical spreading depolarization that arose frequently from the peritumoral region may provide a mechanism for transient neurological deficits. Early blockade of glial xCT activity inhibited later seizures, and genomic reduction of host brain excitability by deleting microtubule-associated protein Tau suppressed molecular markers of epileptogenesis and seizures. Our studies confirmed xenograft tumor–driven pathobiology and revealed early and late components of tumor-related epileptogenesis in a genetically tractable, immunocompetent mouse model of glioma, allowing the complex dissection of tumor versus host pathogenic seizure mechanisms.